2020
DOI: 10.1186/s10194-020-01145-y
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene-related peptide facilitates sensitization of the vestibular nucleus in a rat model of chronic migraine

Abstract: Background: Vestibular migraine has recently been recognized as a novel subtype of migraine. However, the mechanism that relate vestibular symptoms to migraine had not been well elucidated. Thus, the present study investigated vestibular dysfunction in a rat model of chronic migraine (CM), and to dissect potential mechanisms between migraine and vertigo. Methods: Rats subjected to recurrent intermittent administration of nitroglycerin (NTG) were used as the CM model. Migraine-and vestibular-related behaviors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 59 publications
5
26
0
Order By: Relevance
“…Consistent with previous studies (Zhang et al, 2020), we observed that in mice treated with NTG, head grooming time increased as compared with the vehicle control group on days 3, 5, 7, and 9. Moreover, significant change was detected on day 11 (2 days after stopping NTG injection) (Figure 1B and Supplementary Table 2).…”
Section: Repeated Ntg Injection Induced Photophobia and Increased Head Grooming Timesupporting
confidence: 92%
“…Consistent with previous studies (Zhang et al, 2020), we observed that in mice treated with NTG, head grooming time increased as compared with the vehicle control group on days 3, 5, 7, and 9. Moreover, significant change was detected on day 11 (2 days after stopping NTG injection) (Figure 1B and Supplementary Table 2).…”
Section: Repeated Ntg Injection Induced Photophobia and Increased Head Grooming Timesupporting
confidence: 92%
“…Our previous animal experiments found behavioral manifestations of vestibular injury in chronic migraine models; the development of vestibular injury was consistent with the trend in the development of allodynia, and we observed that the structure of the vestibular afferent terminal organs in a chronic migraine rat model was preserved (36). In addition, the activation of neurons in the spinal trigeminal nucleus and vestibular nucleus in the animal model of chronic migraine, and further, the activation of the trigeminal nucleus in the chronic migraine model were mainly due to the activation of the vestibular nucleus mediated by the spinal trigeminal nucleus (36). These studies suggested that the vestibular disorders associated with chronic migraine may be due to the activation of the trigeminal neurovascular system caused by the activation of the vestibular nucleus during chronic migraine.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies suggested that the etiology of vestibular symptoms in migraine patients may be related to the overlap of the trigeminal nerve and the vestibular pathway (35). Our previous animal experiments found behavioral manifestations of vestibular injury in chronic migraine models; the development of vestibular injury was consistent with the trend in the development of allodynia, and we observed that the structure of the vestibular afferent terminal organs in a chronic migraine rat model was preserved (36). In addition, the activation of neurons in the spinal trigeminal nucleus and vestibular nucleus in the animal model of chronic migraine, and further, the activation of the trigeminal nucleus in the chronic migraine model were mainly due to the activation of the vestibular nucleus mediated by the spinal trigeminal nucleus (36).…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, hyperalgesia was ameliorated by knocking down CGRP with short hairpin RNA. 84 In a rat model of migraine (glass micropipette inserted into the visual cortex), a propagating wave of depolarization was induced with a resultant increase in the firing rate of spinal trigeminal nucleus neurons. 85 The increased firing rate was blocked when rats were pretreated with a CGRP-blocking antibody.…”
Section: Dry Eye and Migraine Share Underlying Pathophysiologymentioning
confidence: 99%